Tailoring Organic Apples by Cultivar Selection, Production System, and Post-harvest Treatment to Improve Quality and Storage Life - Tahir, Ibrahim I.; Nybom, Hilde (HortScience, 2013)
A series of pre- and post-harvest experiments were conducted to enhance apple tree productivity and improve fruit quality and storage life by altering production system and post-harvest treatments in an organic orchard. Increasing the light distribution and carbohydrate uptake (summer pruning and covering the orchard ground with reflective textile) improved tree productivity, fruit color, content of anthocyanin, ascorbic acid, and total phenolic compounds and reduced incidence of fungal storage diseases. Optimal harvesting time could be determined from the starch index in some cultivars, whereas the Streif index [firmness (soluble solids concentration × starch hydrolysis score) −1 ] was more accurate for other cultivars. In yet others, titratable acidity and flesh firmness also produced important information. By contrast, soluble solids concentration and skin color are not useful as a result of their sensitivity to weather conditions and light intensity. Post-harvest fruit treatment with hot water (46 °C for 120 seconds) decreased fungal decay during storage in two cultivars, whereas spraying the fruit with 10% ethanol decreased fungal decay in all investigated cultivars. Optimization of storage conditions [cultivar-specific controlled atmosphere (CA) and ultra-low oxygen (ULO) storage procedures] maintained fruit quality and reduced the amount of fungal decay.